The first complete mitochondrial genome from the family Solasteridae, Crossaster papposus (Echinodermata, Asteroidea) - Nam, Sang-Eun (Mitochondrial DNA B Resour, 2021)
The common sunstar, Crossaster papposus, belongs to the family Solasteridae whose ordinal classification has been unstable. Here, for the first time, we assembled and annotated the complete mitochondrial genome of the common sunstar, C. papposus Linnaeus, 1767. The circular genome of C. papposus is 16,335 bp in length and contains 13 protein-coding genes (PCGs), 22 transfer RNA (tRNA) genes, a control region, and large and small ribosomal subunits. The overall genomic structure and gene arrangement were identical to the reported mitochondrial genomes of sea star species, and a phylogenetic analysis of 13 PCGs recovers a closest relationship with the derived cluster of the paraphyletic order Valvatida.